2020
DOI: 10.3389/fenvs.2020.00153
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of 87Sr/86Sr During Wine-Making of White Wines: A Geochemical Fingerprint of Geographical Provenance and Quality Production

Abstract: The measuring of 87 Sr/ 86 Sr in wine, grape, and bioavailable soil fraction samples with the same uncertainty of geological materials allows fully comparing the whole wineproduction chain with the peculiar geochemical isotope signature of any geographic area. Indeed, this signature is the same as the final product inherited by the soil bioavailable fraction and, in turn, by the geological substratum of the vineyard. On the other hand, the few data available in literature that referred to white wines cast doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…The elongated shape of quartz is entirely convincing of a noneolian origin and it is unrealistic, on the other hand, to image that eolian quartz choses to deposit only in the clayey soils without leucite and analcime. This information on the origin of quartz in the Colli Albani soils is of great significate for future researches focused on the traceability of high-quality wines on the basis of isotope ratios (Tescione et al 2020).…”
Section: Discussionmentioning
confidence: 84%
“…The elongated shape of quartz is entirely convincing of a noneolian origin and it is unrealistic, on the other hand, to image that eolian quartz choses to deposit only in the clayey soils without leucite and analcime. This information on the origin of quartz in the Colli Albani soils is of great significate for future researches focused on the traceability of high-quality wines on the basis of isotope ratios (Tescione et al 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Wine processing is another source of potential isotopic modification agents, e.g., nanofiltration to reduce the ethanol content, the addition of bentonite (a smectite clay) to 'clear' wines of proteins and ageing in wood barrels for flavour enhancement [18,41,42]. Multiple studies of these techniques have concluded that the isotopic signature is preserved throughout the process, from soil to grape through to the finished product.…”
Section: Anthropogenic Inputs-farming Clearing and Ageing Winesmentioning
confidence: 99%
“…This is reinforced in Tenerife DO wines. Bentonite fining agents have high Sr concentrations, e.g., 59 ppm [41], and are added to white wines, so they may show a clay influence in their Sr signatures. Tenerife white wines have lower Sr concentrations (generally < 1 ppm and smaller ranges) than red wines in all five DO regions.…”
Section: Anthropogenic Inputs-farming Clearing and Ageing Winesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bentonite treatments are responsible for various elements deposited in the wines [ 25 , 28 , 29 ]. The geographical traceability of wines was investigated using different methodologies on the basis of multivariate analysis of natural chemical composition data (inorganic or organic parameters) and the 87 Sr/ 86 Sr isotopic signature [ 30 , 31 , 32 ]. Tracing sources of heavy metal pollution from wines is widely used as a pollution tracer, especially in the case of lead, which is recognized as a severe threat to human and terrestrial environmental health.…”
Section: Introductionmentioning
confidence: 99%